2017
DOI: 10.1111/cdep.12240
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Understanding: Relationships With Arithmetic and Reading Development

Abstract: Pattern understanding (patterning) is commonly taught in early years classrooms. However, the relationship between patterning and academic attainment is not well understood. Studies investigating children's pattern understanding are reviewed. There is some evidence to suggest that pattern understanding is causally related to acquiring math and reading skills. However, much of the evidence is weak and these conclusions remain tentative. Future studies of the relationship between patterning and other skills need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 28 publications
1
24
0
2
Order By: Relevance
“…The empirical research published previously (c.f. reviews by Burgoyne et al, 2017;Pasnak, 2017) has consistently shown relations between the patterning and mathematics scores of both preschoolers and first graders on a variety of mathematics measures, whether the patterns were simple alternations or complex like those used in the present research. However, this experiment and that of Shriver et al (2017) are the only ones conducted with kindergartners, and neither shows such a relationship.…”
Section: Discussionsupporting
confidence: 50%
“…The empirical research published previously (c.f. reviews by Burgoyne et al, 2017;Pasnak, 2017) has consistently shown relations between the patterning and mathematics scores of both preschoolers and first graders on a variety of mathematics measures, whether the patterns were simple alternations or complex like those used in the present research. However, this experiment and that of Shriver et al (2017) are the only ones conducted with kindergartners, and neither shows such a relationship.…”
Section: Discussionsupporting
confidence: 50%
“…It is known that patterning facilitates later mathematics performance and is related to some early reading skills (cf. reviews by Burgoyne et al, 2017 ; Pasnak, 2017 ). Elementary school curricula already place emphasis on detecting patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The case for reading is, as Burgoyne et al (2017) suggest, not quite so well established, but seems fairly strong. Hendricks et al (2006) found a significant effect of instruction with a huge assortment of patterns on the written language scale of the Diagnostic Achievement Battery-2, and Kidd et al (2014) found that an intervention also employing numerous types of patterns produced significant differences on the Gray Oral Reading Test-4 (GORT), the Test of Word Reading Ability (TOWRE), and the Test of Early Reading Ability-3 (TERA).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations